PENGARUH UMUR DAN PENYAKIT PENYERTA TERHADAP RESIKO INFEKSI LUKA OPERASI PADA PASIEN BEDAH GASTROINTESTINAL - Faridah, Imaniar Noor; Andayani, Tri Murti; Inayati, Inayati (Universitas Ahmad Dahlan, 2012)
Surgical Site Infection/SSI is the result of the contamination of bacteria whichenter the body during surgery. High risk of SSI is occured in gastrointestinal surgeryand influenced by the characteristics of the patients such as age and comorbidity sincethey deal with immunity system of the body. The research was aimed to identity theinfluence of age and comorbidity to the high risk of SSI in gastrointestinal surgerypatients. The research was a cross sectional research conducted prospectively at PKUMuhammadiyah Hospital Yogyakarta from January to March 2012. The researchsubjects were all inpatients undergoing gastrointestinal surgery, having visiblesurgical site and using antibiotic to prevent surgical site infection. There are 68patients in the research. Data that were analyzed comprised the characteristics ofpatients such as age and congenital disease to the risk of surgical site infection. Theresult of this research indicated that 2 patients (2,94%) suffering SSI. Based on the age,SSI happened to 2 patients in the age range of 41-60 years old. However, based on thestatistical result, there was no correlation between age and the existence of SSI(p>0.05). SSI also occured in 2 patients with comorbidity. However, there wascorrelation between the existence of comorbidity and SSI (p<0.05).